Dental anxiety and pain related to ART - Soraya Coelho Leal; Danielle Matos de Menezes Abreu; Jo E. Frencken (University of São Paulo, 2009)
Atraumatic Restorative Treatment (ART) is considered to be well accepted, both by children and by adult patients. The objective of this review is to present and discuss the evidence regarding the acceptability of ART, from the patient's perspective. Aspects related to dental anxiety/fear and pain/discomfort have been highlighted, to facilitate better understanding and use of the information available in the literature. CONCLUSIONS: The ART approach has been shown to cause less discomfort than other conventional approaches and is, therefore, considered a very promising "atraumatic" management approach for cavitated carious lesions in children, anxious adults and possibly, for dental-phobic patients.